Distinct proteomic profiles of plasma-derived extracellular vesicles in healthy, benign, and triple-negative breast cancer: candidate biomarkers for liquid biopsy - Tamarindo, G. H.; Novais, A. A.; Frigieri, B. M. [UNESP]; Alves, D. L.; de Souza, C. A.; Amadeu, A.; da Silveira, J. C.; Souza, F. F. [UNESP]; Bordin, N. A.; Chuffa, L. G. A. [UNESP]; Zuccari, D. A. P. C. (Springer Nature, 2025)
Extracellular vesicles (EVs) derived from plasma, measuring up to 150 nm, act as molecular messengers transmitting critical information to recipient cells, making them valuable candidates for liquid biopsy applications in cancer diagnostics. Triple-negative breast cancer (TNBC) is particularly challenging due to its aggressive nature, metastasis potential, and limited treatment options. This study aimed to identify EV-associated proteins in blood samples that could serve as potential TNBC biomarkers. Using mass spectrometry-based proteomic analysis, we detected unique and differentially expressed proteins across healthy individuals, patients with benign breast conditions, and those with TNBC. While EVs size and concentration showed no differences, the proteomic profile varied significantly among these groups. Several immune-related proteins were found exclusively in healthy individuals but were diminished in both benign and malignant cases. We also assessed the impact of surgery on EVs protein content and identified Histone H2A as a TNBC-specific marker present before surgery. Its expression was further validated through immunohistochemistry and Western blotting in TNBC biopsies and cell lines. Notably, surgical intervention enhanced immune response pathways in TNBC patients. In conclusion, liquid biopsy has the potential to serve as a non-invasive tool for TNBC diagnosis and monitoring, revealing a post-surgery molecular landscape that supports combining immunotherapy with mastectomy.